Servant-spiritual leadership and its relationship with the quality of working life index for teachers at islamic primary educational institutions - Ma’shum Thoyib; Muhamad Bisri Ihwan (Journal of Counseling, Education and Society, 2026)
This study aims to explore teachers’ lived experiences of servant-spiritual leadership and its perceived relationship with job satisfaction, motivation, professional commitment, and Quality of Working Life (QWL) in Islamic educational institutions. The approach used was qualitative, employing a descriptive case study design, with an emphasis on gaining an in-depth understanding of teachers’ experiences within their social and professional contexts. This research was conducted at MI Nurudzolam, Pare, Kediri, East Java, Indonesia, involving 21 participants comprising the principal, vice principal, senior teachers, and junior teachers. Data collection techniques included in-depth interviews, participant observation, and documentation related to leadership practices and the work environment. Data analysis was conducted through data reduction, data presentation, and inductive conclusion drawing, with trustworthiness ensured through source triangulation, method triangulation, and member checking. The findings indicate that servant-spiritual leadership which prioritizes service, empathy, role modeling, and spiritual values is perceived by teachers as strongly associated with increased motivation and professional commitment. Furthermore, this leadership style is associated with improved job satisfaction and the psychological, social, and professional meaning aspects of teachers’ quality of work life (QWL). A supportive work environment, a collaborative culture, and recognition of individual contributions foster a sense of belonging and loyalty among teachers. This research contributes by emphasizing the importance of humanistic and spiritual leadership in enhancing human resource quality and fostering a harmonious work environment in Islamic educational institutions.